Beyond the Chicken: Alternative Avian Models for Developmental Physiological Research - Flores-Santin, Josele; Burggren, Warren W. (Frontiers in Physiology, 2021)
Biomedical research focusing on physiological, morphological, behavioral, and other aspects of development has long depended upon the chicken (Gallus gallus domesticus) as a key animal model that is presumed to be typical of birds and generally applicable to mammals. Yet, the modern chicken in its many forms is the result of artificial selection more intense than almost any other domesticated animal. A consequence of great variation in genotype and phenotype is that some breeds have inherent aberrant physiological and morphological traits that may show up relatively early in development (e.g., hypertension, hyperglycemia, and limb defects in the broiler chickens). While such traits can be useful as models of specific diseases, this high degree of specialization can color general experimental results and affect their translational value. Against this background, in this review we first consider the characteristics that make an animal model attractive for developmental research (e.g., accessibility, ease of rearing, size, fecundity, development rates, genetic variation, etc.). We then explore opportunities presented by the embryo to adult continuum of alternative bird models, including quail, ratites, songbirds, birds of prey, and corvids. We conclude by indicating that expanding developmental studies beyond the chicken model to include additional avian groups will both validate the chicken model as well as potentially identify even more suitable avian models for answering questions applicable to both basic biology and the human condition.